Electro-catalytic oxidation of HMF to FDCA over RuO2/MnO2/CNT catalysts in base-free solution. (3rd November 2021) - Wang, Tianci; Song, Yu; Zhao, Wanna; Zhou, Chunmei; Jin, Yuguang; Wan, Xiaoyue; Dai, Yihu; Yang, Yanhui
Abstract : Up to 72% yield of 2, 5-furandicarboxylic acid was achieved in a neutral electrolyte through the electro-oxidation of 5-hydroxymethylfurfural over a ruthenium–manganese mixed oxide catalyst. Abstract : The oxidation of 5-hydroxymethylfurfural (HMF) to 2, 5-furandicarboxylic acid (FDCA) is one of the most attractive reactions to establish a sustainable chemical process based on biomass resources. In this work, a CNT-supported ruthenium–manganese oxide nano-catalyst (RuO2 /MnO2 /CNT) was employed for the electro-catalytic oxidation of HMF in base-free aqueous solution. The activity test showed that α-MnO2 can effectively promote the activity of RuO2 in the oxidation of HMF. In comparison with RuO2 /CNT, RuO2 /MnO2 /CNT possessed a lower activation energy and more than twice the FDCA formation rate. Under the optimized reaction conditions, the RuO2 /MnO2 /CNT catalyst afforded a FDCA yield of 72.1% in a 0.1 M K2 SO4 aqueous solution at a 0.9 V ( vs. Ag/AgCl) applied potential. To our knowledge, this is the first demonstration of FDCA formation as the primary product with high yield in an initially neutral electrolyte. The product FDCA can be easily separated after cooling the reaction solution to room temperature.